RANCANG BANGUN SISTEM KEAMANAN SEPEDA MOTOR MENGGUNAKAN RFID DAN PERSONAL IDENTIFICATION NUMBER (PIN) BERBASIS MIKROKONTROLER ATMEGA16 - Galang Yudha Murih Raharja; Padjar Setyobudi (Elkom : Jurnal Elektronika dan Komputer, 2019)
The increase in motorized vehicles in urban areas is followed by an increase in cases of motorcycle theft due to the lack of public awareness about the motorcycle security system. The intensity of motorcycle theft with its disclosure is still far in comparison. Crime will also increase, such as cases of theft of motor vehicles, especially motorbikes. Cases of motorcycle theft still often occur, this happens because there is still a lack of security systems contained in motorized vehicles that only use ignition. the existence of an alternative safety system is needed because the average key of a conventional motorcycle is easily penetrated by thieves. A double motorcycle safety device (Doble Smart Lock) composed of an RFID and Personal Identification Number (PIN) and an ATMega microcontroller. This system serves to provide two-stage security. The first stage is a microcontroller in the form of a PIN and the second stage is an RFID system. If the first stage breaks then it will enter the second stage, namely the RFID system The results in the form of a main tool for motorcycle management consists of: Power supply, RFID Card, RFID Reader, Personal Identification Number (PIN), IC / Microcontroller ATMega and already running. The system testing process shows the number 3 in the expert validation test and the number 3 in the expert validation trial. Based on the above calculation, it can be concluded that the validation results from the expert show that the value of 3 is between 2 - 3, which is classified in the valid category. The system process shows the number 3 in the expert validation and the number 2.9 in the validation trial of the user. Based on the above calculation, it can be concluded that the validation results from the user point to a value of 2.9 between 2 - 3 which is classified in the valid category.